Analisis Kognitif Siswa Berdasarkan Kerangka Formulate Employ Interpret pada Soal PISA Level 4 - Husnul Khotimah; Mulianah Mulianah; Abdul Rahman; Bernard Bernard (Mandalika Mathematics and Educations Journal, 2026)
This study aims to analyze students’ difficulties in solving PISA Level 4 equivalent mathematical literacy tasks based on the Formulate, Employ, and Interpret (FEI) processes and to identify scaffolding implications at each stage. A descriptive design with quantitative and qualitative approaches was employed involving 28 ninth-grade junior high school students who worked on four PISA Level 4 equivalent tasks. Quantitative analysis was used to map students’ achievement profiles across the FEI processes, while qualitative analysis examined selected students’ written solution traces. The results indicate that students’ difficulties were most prominent at the formulate stage, as reflected in incomplete mathematical representations, although some students were able to carry out procedures (employ) and obtain correct final answers. Procedural errors and conceptual misconceptions persisted at the employ stage, whereas at the interpret stage students tended to stop at numerical results without adequately relating them to the problem context. These findings suggest that the FEI processes are interconnected and conceptually hierarchical, although they are not always explicitly articulated in students’ written responses, and provide a basis for future action-oriented research aimed at improving instruction and students’ performance in PISA assessments.